EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI VIDEO INTERAKTIF BERBANTUAN QUIZIZZ UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Indri Astuti, Retno; Sunarso, Ali; Isdaryanti, Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aimed to determine the effectiveness of using interactive videos assisted by quizizz in the learning process to improve mathematical problem-solving skills and student learning outcomes. The research design used in this study was True Experimental Design. This research was conducted at SD Negeri Ujungrusi 04 Tegal Regency with a population of fourth-grade students totaling 33 students as the experimental class and SD Negeri Harjosari Lor 01 totaling 30 students as the control class. The calculation results for the improvement of problem-solving obtained t-count 5.39 < t-table 1.64. Then the results of Z-count to measure the completeness of learning outcomes obtained Z-count of the experimental class is 2.241225> Z table 1.64. Calculation of student learning outcomes obtained from the results of the T-Test sig. (2-tailed) 0.000 <0.05, Ho is rejected. This means that the average value of the mathematical problem-solving ability of the experimental class is better than the control class. The N-gain calculation for the experimental class is 30.2430 or 0.302 including in the medium category. So it can be concluded that using interactive videos assisted by quizizz in learning mathematics can improve students' problem-solving skills and learning outcomes.